Betalain-rich dragon fruit (pitaya) consumption improves vascular function in men and women: a double-blind, randomized controlled crossover trial. Issue 5 (10th March 2022) - Cheok, Alex; Xu, Yifan; Zhang, Zicheng; Caton, Paul W; Rodriguez-Mateos, Ana
ABSTRACT: Background: Betalains are natural red color pigments abundant in red-fleshed dragon fruit ( Hylocereus polyrhizus ). Recent research has shown that dragon fruit consumption may help improve blood glucose and lipid profile. However, investigations of its cardioprotective properties in human trials, especially in nutritionally achievable amounts, remain nonexistent. Objectives: The aim of this study was to investigate the effects of acute and short-term consumption of dragon fruit on vascular function in a healthy population. Methods: A randomized, double-blind, placebo-controlled, crossover trial was conducted in 19 young, healthy, nonsmoking men and women assigned to consume 24 g whole dragon fruit powder (33 mg betalains) or a nutrient-matched placebo, daily for 14 d. Flow-mediated dilation (FMD), arterial stiffness, and blood pressure (BP) were measured at 0 h, 1 h, 2 h, 3 h, and 4 h and finally at 14 d after daily consumption. Results: A total of 18 participants completed the trial. Dragon fruit consumption significantly improved acute FMD at 2 h (+0.8 ± 0.3%, P = 0.01), 3 h (+1.0 ± 0.3%, P = 0.001), and 4 h (+1.3 ± 0.4%, P < 0.001) postconsumption compared with placebo. This effect was sustained up until 14 d (+1.3 ± 0.2%, P < 0.001). Pulse-wave velocity was acutely significantly reduced at 3 h (–0.5 ± 0.2 m/s, P = 0.003), whereas augmentation index (AIx) also improved after 14 d (–7.0 ± 3.3%, P = 0.02) when compared with placebo. No differences were found in either peripheral or central BP across all time points. Conclusions: Acute and short-term consumption of dragon fruit in dietary achievable amounts improved endothelial function and arterial stiffness in healthy individuals. This implies that regular dragon fruit consumption may have a meaningful impact on cardiovascular disease risk likely due to the high betalain content. This trial was registered at ClinicalTrials.gov as NCT03995602. Graphical Abstract: